THE EFFECT OF PROGRESSIVE MUSCLE RELAXATION TECHNIQUE EXERCISE AGAINST RHEUMATOID ARTHRITIS PAIN INTENSITY ON ELDERLY (Studies in the elderly Social Welfare Institution of Darus Syifa Jombang) - . Suliana; . Darsini; Agus Muslim (STIKES Insan Cendekia Medika Jombang, 2013)
Progressive muscle relaxation technique exercises is a non-pharmacological treatment which one of the usesto lower or reduces pain (rheumatism) arthritis reumatoid on elderly. The purpose of this research was toanalyze the effent of Progressive muscle relaxation technique exercises Against Rheumatoid Arthritis PainIntensity on elderly. This research design used was one group pre-post test design. The populastion in thisresearch was all elderly who live in the Darus Syifa Jombang and suffer arthritis reumatoid. Samplingtechnique used was total sampling (sampling saturated) with the sample as many as 17 respondents. Theindependents variable was progressive muscle relaxation technique exercises while the dependent variablewas Pain Intensity. The instruments in this research used SOP (Standart Operarational Procedure) forrelaxation techniques and the observation sheet to overview level pain scale before and after treatmentrelaxation techniques. With data processing by editing, coding, scoring, tabulating and statistic test usedwilcoxon. Based on results of the research that’s respondents before got before getting treatment experiencedpain intensity majority as many as 8 (47,1%) and after getting treatment experienced most of respondentssuffered mild pain intensity as many as 9 (52,9%). Based on test of Wilcoxon Sign Rank Test obtained valueof ρ = 0,000, ρ< α, (0,000 < 0,005), it means that H1 accepted. The conclusion in this research is thatthere’s effect of Progressive muscle relaxation technique exercises Against Rheumatoid Arthritis PainIntensity on elderly in the Darus Syifa foundation Jombang. The researcher argue that there’s positive effectin treatment of progressive muscle relaxation technique training Against Rheumatoid Arthritis Pain Intensityon elderly.